(untitled) (Indian Journal of Arid Horticulture, 2021)
An experiment was conducted at ICAR-National Research Centre on Litchi, Muzaffarpur, Bihar during 2017 and 2018 to assess the response of twenty cultivars of litchi to sun burn and fruit cracking. Result revealed that sun burn and fruit cracking varied from 0 to 13.61% and 0 to 14.57%, respectively. CSL-16 exhibited maximum sun burning (13.61%) and fruit cracking (14.57%) whereas ten cultivars viz., CHL-4, CHL-5, CSL-1, CSL-2, CSL-4, CSL-5, CSL-10, CSL-11, CSL-12 and CSL-18 were found free from sun burn and fruit cracking. Sun burn and fruit cracking started in all susceptible cultivars during 51-56 days after fruit set. Sun burn and fruit cracking in different cultivars were found maximum in last ten to fifteen days of fruit growth and development. Sun burn and fruit cracking were not significantly influenced by orientation of fruits on the tree. All the early ripening cultivars were susceptible to sun burn and fruit cracking while late ripening cultivars exhibited tolerance. Tolerant cultivars can be used in breeding programme for further improvement.